Changes in muscle activation following balance and technique training and a season of Australian football. Issue 3 (May 2015) - Donnelly, C.J.; Elliott, B.C.; Doyle, T.L.A.; Finch, C.F.; Dempsey, A.R.; Lloyd, D.G.
Abstract Objectives Determine if balance and technique training implemented adjunct to 1001 male Australian football players' training influenced the activation/strength of the muscles crossing the knee during pre-planned and unplanned sidestepping. Design Randomized Control Trial. Methods Each Australian football player participated in either 28 weeks of balance and technique training or 'sham' training. Twenty-eight Australian football players (balance and technique training, n = 12; 'sham' training, n = 16) completed biomechanical testing pre-to-post training. Peak knee moments and directed co-contraction ratios in three degrees of freedom, as well as total muscle activation were calculated during pre-planned and unplanned sidestepping. Results No significant differences in muscle activation/strength were observed between the 'sham' training and balance and technique training groups. Following a season of Australian football, knee extensor (p = 0.023) and semimembranosus (p = 0.006) muscle activation increased during both pre-planned sidestepping and unplanned sidestepping. Following a season of Australian football, total muscle activation was 30% lower and peak valgus knee moments 80% greater (p = 0.022) during unplanned sidestepping when compared with pre-planned sidestepping. Conclusions When implemented in a community level training environment, balance and technique training was not effective in changing the activation of the muscles crossing the knee during sidestepping. Following a season of Australian football, players are better able to support both frontal and sagittal plane knee moments. When compared to pre-planned sidestepping, Australian football players may be at increased risk of anterior cruciate ligament injury during unplanned sidestepping in the latter half of an Australian football season.